Women and Artistic Production in the Long Seventeenth Century in the Low Countries - Powell-Warren, Catherine (Early Modern Low Countries, 2025)
The importance of the role of women as artists has been recognised and rightly continues to be researched. However, although there are exceptions, the scholarship that has been produced over the past two decades does not sufficiently challenge patriarchal, male-centric art historical research, with its focus on the so-called ‘creative genius’. The result, whether intentional or not, has been a continued emphasis on so-called stars, exceptional women, and trailblazers. Promising scholarship has focused on the role of women as artisan-makers or considered the gender-specific circumstances in which women operated. This scholarship, while of critical importance, unwittingly validates the assumption that the creation and production of (fine) art in the long seventeenth century in the Low Countries was primarily a man’s affair, with women relegated to more peripheral roles. If we are to truly write an inclusive art history, however, we must be willing to re-examine, expand, and even re-define traditional concepts in art history as they relate to the creation and production of art, pursue interdisciplinarity, and adopt the tools at our disposal, notably technical and object-based art history and the digital humanities.